2003
DOI: 10.1590/s0004-282x2003000500001
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of parahippocampal gyrus in 115 patients with hippocampal sclerosis

Abstract: -Purpose: Analysis of the parahippocampal gyrus (PHG) involvement in 115 patients with hippocampal sclerosis (HS) by MR imaging. The simultaneous occurrence of ipsilateral fornix (F) and mamillary body (MB) volume loss was checked also. These findings were correlated with the side of hippocampal involvement, the sex, patient´s age, and the symptoms onset. Method: The MR images of 115 patients with HS were studied retrospectively. All the examinations were performed on 1.5 T units (SIGNA, GE, Milwaukee, WI) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 5 publications
1
10
0
2
Order By: Relevance
“…Previous studies that have used volumetric region of interest measures in TLE have reported atrophy in extrahippocampal regions of the medial temporal lobe [2,9,12], in the thalamus [34], the entorhinal cortex [6,30], the amygdala [16], the lateral temporal lobe [32] and the cerebellum [40] and throughout other regions of the limbic system [35]. Studies using VBM of the entire brain have confirmed these observations [23] and suggested that hippocampal pathology in TLE is accompanied by widespread limbic pathology.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Previous studies that have used volumetric region of interest measures in TLE have reported atrophy in extrahippocampal regions of the medial temporal lobe [2,9,12], in the thalamus [34], the entorhinal cortex [6,30], the amygdala [16], the lateral temporal lobe [32] and the cerebellum [40] and throughout other regions of the limbic system [35]. Studies using VBM of the entire brain have confirmed these observations [23] and suggested that hippocampal pathology in TLE is accompanied by widespread limbic pathology.…”
Section: Discussionmentioning
confidence: 87%
“…Studies that have used volumetric ROI measures in TLE have reported atrophy not only in the hippocampus but also in the thalamus [34], the cerebellum [40] as well as in extrahippocampal regions of the medial temporal lobe [2,9,12] such as the entorhinal cortex [6,30], the amygdala [16], the lateral temporal lobe [32]. Indeed, in TLE patients with MRI detectable medial temporal sclerosis, atrophy and/or signal change have been reported ■ Abstract Hippocampal sclerosis in temporal lobe epilepsy (TLE) is often associated with hippocampal atrophy.…”
Section: Introductionmentioning
confidence: 99%
“…The key role of this region is memory encoding and retrieval. Abnormalities may indicate underlying conditions, such as schizophrenia, Alzheimer’s disease, and hippocampal sclerosis (Ferreira et al, 2003 ). The observation of hyper-activation in the parahippocampal gyrus is consistent with the finding of Dr Maki leading investigators that women receiving HT exhibit decreased regional cerebral blood flow in the right precuneus, the dorsal frontal gyrus, and the parahippocampal gyrus during a verbal memory task (Resnick et al, 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…tarafından, hipokampal atrofisi olan 115 hastanın %37'sinde ipsilateral parahipokampal girus (PHG) atrofisi görülebileceği bildirilmiştir. 26 Yine bilateral talamus volumlerinin incelendiği iki ayrı çalışmada, sklerotik hipokampusun ipsilateralindeki talamik yapılarda hücresel kayıp ve atrofi ile uyumlu bulgular elde edilmiş-tir. 27,28 Çalışmamızda da, her iki hasta grubunda ipsilateral amigdala, PHG ve talamus volumlerinin kontrol grubuna göre anlamlı düzeyde düşük olduğu izlendi.…”
Section: Discussionunclassified
“…Çalışmamıza benzer bir şekilde MTLE-HS tanısı alan hastaların MRV ile değerlen-dirildiği bir çalışmada, 20 yıldan daha uzun süreli hastalık öyküsü olan bireylerde PHG volumlerinin anlamlı derecede düşük olduğu saptanmış, ve bu nedenle MTLE-HS saptanan kişilerde PHG alanı-nın da incelenmesi gerektiği ileri sürülmüştür. 26 Çalışmamızda artmış nöbet sıklığı ile sol amigdala volumü arasında negatif yönde korelasyon saptandı. Amigdala volumü ve nöbet özellikleri arasındaki ilişki konusunda literatürde farklı sonuçlar mevcuttur.…”
Section: Fk (+) (N=12) Fk (-) (N=16) Punclassified